2002
DOI: 10.21273/jashs.127.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions of Pillar (Columnar), Compact, and Dwarf Peach Tree Genotypes

Abstract: A study was conducted to determine genetic control of the columnar or pillar (PI) growth habit, and to evaluate the effects of interactions of various genes that influence peach [Prunus persica (L.) Batsch (Peach Group)] growth habit. The PI habit (brbr) examined in this study was inherited as a monogenic trait expressing incomplete dominance. The heterozygous Brbr derived from crosses between standard (ST) and PI genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…But, to gain an advantage from the dwarf trait, breeders should in future focus not only on fruit quality, but also on characters such as internode length and leaf size, manipulating them to improve the agronomic characteristics of the dwarf tree. There appear to be ample possibilities of genetically manipulating peach tree growth habit and developing new grow types more suited for commercial peach production (Scorza et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…But, to gain an advantage from the dwarf trait, breeders should in future focus not only on fruit quality, but also on characters such as internode length and leaf size, manipulating them to improve the agronomic characteristics of the dwarf tree. There appear to be ample possibilities of genetically manipulating peach tree growth habit and developing new grow types more suited for commercial peach production (Scorza et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although br/br trees have an entirely columnar or pillar appearance, heterozygous individuals show a more spreading 'upright' phenotype ( Fig. 2f) (Scorza et al, 1989(Scorza et al, , 2002Tworkoski & Scorza, 2001). Physiological studies have shown that pillar peach trees display a range of physical alterations, including shorter lateral shoots (a result of shorter internodes), smaller stem diameter, decreased sylleptic branching and narrow crotch angles (Tworkoski & Scorza, 2001;Tworkoski et al, 2006).…”
Section: Pillar Peachmentioning
confidence: 99%
“…Some dwarf phenotypes found in peach are shown in Fig. 2(h,i) (Scorza et al, 2002;Fideghelli et al, 2003). Dwarfism in plants is typically associated with reduced growth because of shorter internodesindicating a decreased ability to elongate and/or a reduction in cell division (Ross et al, 2005).…”
Section: Dwarf Growth Habitmentioning
confidence: 99%
See 1 more Smart Citation
“…Peach pillar (PI), also known as columnar or broom, is controlled by a recessive allele at the br locus (Chaparro et al 1994;Rajapakse et al 1995;Scorza et al 2002;Werner and Chaparro 2005) on peach LG-2 (Sajer et al 2011;Sosinski et al 2000). Peach chromosome-2 shows strong synteny with apple chromosomes 1, 2 and 7 (Illa et al 2011), but not with apple chromosome-10 where the Co locus resides.…”
Section: Introductionmentioning
confidence: 99%